Minimally invasive surgery: has it come of age?. Issue 1 (February 2023) - Pang, Joe Hwong; Spalding, Lynette; Pasapula, Chandra
Abstract: Open techniques for foot surgery are well established. Minimally invasive surgery (MIS) offers the potential of less morbidity, scarring and quicker recovery. Small incisions reduce surgical trauma, improving recovery and decreasing rehabilitation times. Evaluation of the literature enables us to assess the benefits of MIS over existing open techniques to support its widespread adoption. Our aim was to assess levels of evidence for the use of MIS surgery in various aspects of foot and ankle surgery. In the field of hallux valgus correction, randomized control trials, or prospective cohort studies have provided level 1 evidence for the use of MIS techniques. Other aspects of foot and ankle surgery are mainly dominated by technical descriptions or case series. MIS techniques have the opportunity to provide satisfactory outcomes in many fields, with many domains reporting promising results. However, more studies are required to provide good level 1/2 evidence for comparative analysis to equivalent open techniques and establish their true benefit. More trials, longer follow-up and larger patient series may provide more meaningful data to justify MIS's use. Comparative analysis of MIS's true benefit compared to open surgery in areas of foot and ankle surgery outside hallux valgus has yet to be established with higher levels of evidence lacking.